Sexuality and contraceptive knowledge in university students: instrument development and psychometric analysis using item response theory - Sebastian Sanz-Martos; Isabel M. López-Medina; Cristina Álvarez-García; Carmen Álvarez-Nieto (BMC, 2019)
Abstract Background As a consequence of biological, psychological and social changes during puberty, youth is a period characterized by impulsiveness and risk-taking. Members of this population often feel invulnerable and have a strong motivation to explore their identity. A good level of knowledge is necessary to allow young people to experience their sexuality in a healthy way, without associated risks. In our environment there is currently no valid Spanish-language tool to measure the level of knowledge about sexuality and contraception. This study sought to develop and test the psychometric properties of a new sexuality and contraception knowledge instrument. Methods This is a cross-sectional study to validate the sexuality and contraception knowledge instrument. The validation process followed four phases: (1) development of the instrument, (2) content validation by an expert panel, (3) pilot test and (4) psychometric analysis of the instrument using item response theory according to the Rasch model. The validation process took place from September 2017 to February 2018. Results The sample included 387 students enrolled at the Nursing and Law degrees from the University of Jaen. The final instrument was made up of 15 items. All of the items presented good adaptation values with respect to the model. The scale showed good fit and reliability: 0.99 for items and 0.74 for people. The temporal stability of the scale was calculated using test-retest, obtaining a value of 0.81 (CI 0.692-0.888). The construct validity showed the one-dimensionality of the construct, while the discriminant validity obtained good results, so the scale appears to be able to differentiate between participants with low or high levels of knowledge. Conclusion The results suggest the Sexuality and Contraception Knowledge Instrument is psychometrically valid and reliable for measuring the knowledge level concerning sexuality and contraceptive methods in young university students.